Cyclodextrins with Multiple Pyrenyl Groups: An Approach to Organic Molecules Exhibiting Bright Excimer Circularly Polarized Luminescence. (29th December 2021) - Shigemitsu, Hajime; Kawakami, Kosei; Nagata, Yuuya; Kajiwara, Rikuo; Yamada, Shintaro; Mori, Tadashi; Kida, Toshiyuki
Abstract: We report a simple and effective approach to organic molecules exhibiting bright circularly polarized luminescence (CPL) by combining a chiral cyclic molecular scaffold and multiple excimer‐enabling moieties. An α‐cyclodextrin (CyD ) scaffold was modified with six pyrenyl groups to obtain pyrene–cyclodextrins (PCD s) in a one‐step synthesis from commercially available compounds. The PCDs exhibited high molar extinction coefficients (ϵ≈10 5 M −1 cm −1 ), polarized emission with a good dissymmetry factor (|glum |≈10 −2 ), and quantum yield (Φf ≈0.5). Owing to the excellent photophysical properties of the PCDs, the circularly polarized luminescence brightness (BCPL ) reached 340 M −1 cm −1 . Photophysical and chiroptical studies of the PCD s with only five pyrene units and with linkers of various lengths connecting the CyD with the pyrene units revealed that the formation of a pyrene excimer in a spatially crowded environment is crucial for CPL anisotropy. This study paves the way for the development of bright CPL organic molecules. Abstract : Cyclodextrins with multiple pyrene units exhibited bright circularly polarized luminescence (CPL). Owing to their good molar extinction coefficients ( ϵ ≈10 5 M ‐1 cm ‐1 ), polarized emission with a good dissymmetry factor (| g lum |≈10 ‐2 ), and quantum yield ( Φ f ≈0.5), the CPL brightness ( B CPL ) reached 340 M ‐1 cm ‐1 .